GARAP TARI CAKIL GAYA SURAKARTA - Wahyudi, Didik Bambang (Acintya, 2023)
This reseach, briefly, Garap Tari Cakil in Surakarta, were understanding and explaining descriptively existence and development of Cakil dance as genres; wireng, fragmen, wireng pethilan and also as a part of traditional dance drama (wayang orang panggung). Descriptive explanation consist of 1) historical background, function and existence of cakil in shadow puppet player (pertunjukan wayang kulit; 2) Cakil development as a dance performance including form and meaning in a discussion about the dance elements become a unity in garap (totality of form and idea) of the performance. This study wanted to explain the existence of cakil dance through the times in garap of the performance. 3) the existence of people who influenced to the change and development of this dance.